2022
DOI: 10.3390/nu14040748
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of L-Ornithine-L-Aspartate Is Associated with Distinct Microbiome and Metabolome Changes in Cirrhosis

Abstract: L-ornithine L-aspartate (LOLA) is administered as a therapeutic and/or preventive strategy against hepatic encephalopathy either intravenously or orally in patients with liver cirrhosis. Here, we analyzed how LOLA influences the microbiome and metabolome of patients with liver cirrhosis. We retrospectively analyzed the stool microbiome, stool, urine and serum metabolome as well as markers for gut permeability, inflammation and muscle metabolism of 15 cirrhosis patients treated orally with LOLA for at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…So far, only a recent work analyzed microbiota changes at LOLA treatment. Horvath et al [ 21 ], 2022, evaluated the microbiota composition of 15 cirrhotic patients treated or not treated with LOLA. The authors reported no differences in alpha and beta diversities, but significant differential abundances in two genera ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a recent work analyzed microbiota changes at LOLA treatment. Horvath et al [ 21 ], 2022, evaluated the microbiota composition of 15 cirrhotic patients treated or not treated with LOLA. The authors reported no differences in alpha and beta diversities, but significant differential abundances in two genera ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…LOLA, when added to other anti-HE treatments, has been proven effective and should be used in therapy without hesitation. Moreover, beyond HE treatment, Horvath et al recently observed LOLA's positive impact on enhancing the microbiome and beneficial metabolomic changes, such as IGF-1 levels, in liver disease patients 27 .…”
Section: Discussionmentioning
confidence: 99%